Women Victim of Violence and Food Security in Indonesia-Timor Leste Border Region: A Gender Equality Perspective - Mbiri, Adeodata Laniria Charla Barros; Siba , M. Angela Merici; Kalembang, Elpius; Bria, Fridus; Kristoforus Taekab, Yosef (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2026)
This study examines how women survivors of domestic violence in the Indonesia–Timor-Leste border district of North Central Timor (TTU), Nusa Tenggara Timur, contribute to household food security while advancing gender equality. Using interactionist role theory as an analytical lens, we trace how empowerment initiatives facilitated by the local NGO YABIKU and the TTU Office for Women’s Empowerment and Child Protection enable survivors to renegotiate the socially imposed “victim” role. Qualitative data were collected through observation, interviews, and document review and analyzed using Creswell’s coding and interpretation procedures. The findings show that violence in TTU is reinforced by patriarchal norms and weak household economies; therefore, livelihood-oriented empowerment becomes a practical form of violence mitigation. Survivors enact new roles through household horticulture, small livestock raising, local-food microenterprises, and environmental stewardship, improving daily food access and generating income. Collective organizing also produced institutional change, including Local Regulation No. 14 of 2016 on women’s protection and the formation of paralegal networks that assist violence cases. Overall, the study demonstrates that role transformation through food-security activities strengthens women’s agency, reduces vulnerability to repeated violence, and supports more equitable community governance in the border region